Pengaruh Premi Asuransi dan Kualitas Pelayanan Terhadap Kepuasan Nasabah Asuransi Pendidikan (Studi Kasus pada Asuransi Jiwa Bersama Bumiputera 1912 Kantor Cabang Eksekutif Semarang ) - Adisaputro, Aristyo; Suryoko, Sri; Nugraha, Hari Susanta (Jurnal Ilmu Administrasi Bisnis, 2013)
Companies which engaged in trade and services, customer  plays a very important role. As companies which strive to meet the needs and desires of its customers, the company's survival depends on the behavior of the consumers. Several factors will determine the insurance customer satisfaction including the appropriate price and the quality of service. Along with the increasing of public welfare so the consumption on other basic needs such as foods, clothes and houses have also increased. A need on insurance services increasingly perceived, not only for individuals but also for business in Indonesia. It is called as the tremendous progress in the services sector of the indonesia insurance industry  which has  very tight competition. The number of competitors in this business , makes insurance companies should be able to provide a particular advantage.the advantage can be accomplished if there are available informations of the consumer market. To face the competition, AJB Bumiputera 1912 KCE Semarang needs an innovation and improvement in terms of insurance premiums and service qualities. The problem of this study is the reduction in the amount of customers. The type of the research is explanatory research, with the samples are 90 respondents through purposive sampling technique. Analysis techniques used validity, reliability testing, simple linear regression, multiple linear regression, t test and F test with SPSS tools 16. The result of this study showed insurance premiums and quality services of AJB Bumiputera 1912 KCE Semarang can be quite good. Customer satisfaction was also increased. The amount of insurance premiums’ influence on customer satisfaction was 68.1%. The magnitude of the effect of service quality on customer satisfaction was 79.3%. Simultaneously, the influence of insurance premiums and service quality was 80.9%. it means, if the insurance premiums and quality service are better, it will make a result on the significant increase of the consumer  satisfaction.According to the data analysis it can be concluded that partially or simultaneously insurance premiums and service quality significantly make an effect on customer satisfaction and they have a tight and strong level of the relationship. For your suggestion,  Company needs to add the long term contracts as well as reduce the risk of benefits. if the risk of benefits are so much, the premium will be more expensive, but if it is less, the cost of insurance premiums can be lower and make the claims complaint handling standard system which to be a referral for the  agents when they get a claims complaint, in addition, company needs to conduct trainings for employees to enhance their skills, especially,  techniques in how to convey information well and hone verbal skills in conveying information.